KONTRIBUSI KETERAMPILAN MEMBACA PEMAHAMAN TEKS ANEKDOT TERHADAP KETERAMPILAN MENULIS TEKS ANEKDOT SISWA KELAS XI MA NEGERI 3 PADANG - Sepranalita, Yante; Asri, Yasnur (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
ABSTRACTÂ The purpose of this research is three. First, describing the reading skills of anecdotal text students XI MA Negeri 3 Padang. Secondly, it describes the writing skills of anecdotal text students XI MA Negeri 3 Padang. Third, describing the contribution of reading skills of anecdotal text to the writing skills of anecdotal text students XI MA Negeri 3 Padang. This type of research is quantitative by a descriptive method. The design used in this study is design contributions. The population of this study is the XI MA Negeri 3 class students enrolled in the 2018/2019 school year, with 250 students. The samples in this study were determined by simple random sampling 25% of the population, which is 61 students. This research Data in the form of scores of test skills reads the understanding of anecdotal text and scores test results of anecdotal text. The Data is obtained through two types of tests i.e. objective tests to measure the reading skills of anecdotal text and test performance to measure anecdotal text writing skills. The results of this study were three. First, the reading skills of understanding anecdotal text students XI MA Negeri 3 Padang are in good qualification (B) with an average value of 85.09. Secondly, the writing skills of anecdote-class students XI MA Negeri 3 Padang are on a good qualifying (BS) with an average of 86.13. Thirdly, there is a contribution of the reading skills of anecdotal text to the writing skills of anecdotal text students XI MA Negeri 3 Padang amounted to 17.56%.Â Kata Kunci:Kontribusi, Keterampilan, Membaca Pemahaman, Menulis, Teks Anekdot